Challenging Preconceptions: Understanding the Employability of Madrassa Graduates - Junejo, Safiullah; Waheed, Usman (IJELR: International Journal of Education, Language, and Religion, 2024)
Madrassas in Pakistan serve as vital institutions for religious education, providing free teaching and accommodation to students from economically disadvantaged backgrounds. However, several Madrassa graduates face financial challenges upon entering the job market as a result of the rapidly changing technological environment. The majority of these graduates get employment in low-wage roles such as mosque management, madrassa instruction, or labour jobs in profit-oriented enterprises. Madrassas do not include non-religious subjects or technical education in its curriculum, and the government has shown little inclination to support these institutions. An investigation was carried out in the Khairpur area, whereby a sample of 250 Madrassa graduates was selected at random and subjected to a survey in order to analyse these issues. Based on the survey findings, these graduates had difficulties in providing financial assistance for their families. To improve their quality of life, it is recommended that the government provide scholarships and recognise the value of their degrees by granting them credit. The report also indicates that Madrassa graduates should engage in vocational training programmes to facilitate their successful integration into the labour market. In summary, the research highlights the economic challenges that Madrassa graduates in Pakistan encounter and proposes strategies to improve their prospects for the future.